A Review of Building Information Modelling for Construction in Developing Countries. (2016) - Bui, Nam; Merschbrock, Christoph; Munkvold, Bjørn Erik
Abstract: Building Information Modelling (BIM) is widely seen as a catalyst for innovation and productivity in the construction industry. BIM can assist a more sustainable construction process that in turn may contribute to eradicating poverty in developing countries (United Nation Millennium Goals). While BIM is increasingly being adopted in developed countries, implementations in the developing country context are rare. Research has established how construction firms struggle from several limitations having to do with the socio-economic and technological environment found in developing countries. Examples of issues preventing BIM adoption include a shortage of IT-literate personnel as well as an absence of national BIM implementation programs. Based on a review of recent research, this article addresses some of the hurdles and solutions for BIM implementations particular to low- and middle-income economies. Findings include that developing countries' construction firms rely on outsourcing of IT services or developing tweaks or workarounds, like using 'fake' IT licenses, for saving cost and enabling BIM. The article highlights shortcomings of existing research on BIM implementation in developing countries, and may serve as a starting point for researchers interested in how BIM technology can be adopted in a developing country context.